WOMEN’S PROTECTION IN THE PHILOSOPHY OF “THE MAN OF POWER” WITHIN JOINT AND NUCLEAR FAMILY SYSTEMS: A Study in Indonesia and Pakistan - Dewi, Ernita; Furqan, Muhammad; Wan Zakaria, Wan Fariza Alyati; Sain, Zohaib Hasan; Muzakkir, Muzakkir (State Islamic University North Sumatra, 2025)
Pakistani society generally interprets Islamic teachings textually, especially regarding men’s responsibility to protect women, resulting in a strong patriarchal structure. The joint family system places the eldest male as the protector for all members, giving women security in basic needs and housing. This differs from Indonesia, where Muslim communities tend to provide women with greater equality and autonomy. Using a qualitative descriptive method through field and literature research, this study finds that women in Pakistan’s joint family system receive broader support when husbands are absent or irresponsible. In contrast, women in nuclear families—common in Indonesia—often face greater vulnerability due to limited family assistance. While the joint family system enhances women’s protection, it also reinforces dependence on male authority.